مدى إدراك المحاسبين لأثر ممارسات المحاسبة الإبداعية على جودة القوائم المالية - اعمارد. سمية عمار عمران (Aljameai, 2026)
المستخلص: هدفت الدراسة إلى معرفة مدى إدراك المحاسبين لأثر ممارسات المحاسبة الإبداعية على جودة القوائم المالية دراسة تطبيقية على المصرف التجاري الوطني – الإدارة العامة، حيث تم اتباع المنهج الوصفي التحليلي، واستخدام استبانة كوسيلة لجمع البيانات، حيث تم توزيع (45) استبيان على عينة من المحاسبين العاملين بالمصرف استرجع منها (37) استبيانا صالحاً للتحليل بنسبة استرجاع (82%)، وتم تحليل البيانات باستخدام برنامج SPSS، وتوصلت الدراسة إلى أنه يوجد أثر ذو دلالة إحصائية لإدراك المحاسبين بممارسات المحاسبة الإبداعية علي جودة القوائم المالية في المصرف، ويوجد إدراك لدى المحاسبين بممارسات المحاسبة الإبداعية وبأهمية جودة القوائم المالية في المصرف، وأوصت الدراسة بالعمل على ان تكون المعلومات المحاسبية المقدمة في القوائم المالية ملائمة للتنبؤ بالمستقبل، والعمل على ان يقوم المصرف بزيادة ثقافة الشفافية للحد من ممارسة المحاسبة الإبداعية، ويجب أن يتم تطبيق الأسس والمعايير الأخلاقية المهنية للحد من عمليات التلاعب في القوائم المالية. Abstract: The study aimed to examine the extent to which accountants perceive the impact of creative accounting practices on the quality of financial statements, through an applied study on the National Commercial Bank – General Administration. The descriptive-analytical approach was adopted, and a questionnaire was used as a tool for data collection. A total of (45) questionnaires were distributed to a sample of accountants working at the bank, of which (37) valid responses were retrieved for analysis, representing a response rate of (82%). The data were analyzed using the SPSS program. The study found that there is a statistically significant effect of accountants’ awareness of creative accounting practices on the quality of financial statements in the bank. It also revealed that accountants are aware of creative accounting practices and the importance of the quality of financial statements. The study recommended ensuring that accounting information presented in financial statements is suitable for predicting the future, enhancing a culture of transparency within the bank to reduce the practice of creative accounting, and applying professional ethical principles and standards to limit manipulation in financial statements.